TRAIN JOURNEYS OF THE WORLD : A SPECTACULAR VOYAGE OF DISCOVERY ALONG 30 OF THE WORLD'S MOST EXCITING RAIL ROUTES - Gordon, Susan, editor (New York : Automobile Association Development Limited, 1994)
PSZ_KL